PP.40 The potential of digital media to improve fetal and maternal outcomes. (26th April 2013) - O'Higgins, AC; O'Connor, C; Daly, N; Kent, E; Kennelly, M; Turner, M
Abstract : Background: Despite both Ireland and the United Kingdom providing free maternity care to all women, adverse fetal and maternal outcomes remain closely linked to social disadvantage and lack of support during pregnancy. A European survey found 42.4% of respondents had limited functional health literacy, closely liked to economic deprivation. Written information remains the main medium of communication for maternity services. It is likely that many of these messages are not adequately communicated to those most at risk. Objectives: This study examined the use of digital media by pregnant women to access healthcare information for pregnancy. Methods: A survey was distributed to all antenatal patients attending clinics at a large Dublin maternity hospital. Results: Of the 218 women surveyed, 81% attended public clinics and 19% attended private clinics, 60% lived in Dublin and 40% were from surrounding counties, 18% were unemployed. Overall 94% used the internet to access information about pregnancy; 100% of unemployed women use the internet to access healthcare information and 75% of women have a smartphone. Newspapers were read by only 29% of women. All women wanted some form of online/digital support during their pregnancy, including weekly text messages about pregnancy stage-specific issues (cited by 45%), a maternity smartphone App (44%) and a website for feedback regarding their care (42%). Conclusion: Digital media use is widespread across all socioeconomic groups. Healthcare communication in pregnancy should focus on digital communication channels.